Atractylenolide I Induces Apoptosis and Suppresses Glycolysis by Blocking the JAK2/STAT3 Signaling Pathway in Colorectal Cancer Cells - Yanxi Li; Yongpeng Wang; Zhexian Liu; Xingqi Guo; Ziwei Miao; Siping Ma (Frontiers Media S.A., 2020)
Colorectal cancer (CRC) is the third most common cancer worldwide and is associated with a poor clinical outcome and survival. Therefore, the development of novel therapeutic agents for CRC is imperative. Atractylenolide I (AT-I) is a sesquiterpenoid lactone derivative of Rhizoma Atractylodis macrocephalae that exhibits diverse biological activities, including anti-cancer activities. However, the effects and potential mechanism of AT-I in CRC have yet to be fully elucidated. In this study, we aimed to examine the anti-cancer properties of AT-I and the associated functional mechanisms in vitro and in vivo. We found that AT-I treatment significantly suppressed the viability of CRC cell lines and inhibited colony formation, but to a lesser extent in NCM460 cells. Annexin V/PI staining showed that AT-I induced apoptosis in CRC cells, accompanied by increased caspase-3 and PARP-1 cleavage, enhanced expression of Bax, and reduced expression of Bcl-2. Furthermore, AT-I blocked cell glycolysis by inhibiting both glucose uptake and lactate production in CRC cells, and specifically downregulated the expression of the rate-limiting glycolytic enzyme HK2. In contrast, it had no discernable effects on the glycolytic enzymes PFK and PKM2. A mechanistic study revealed that AT-1 negatively regulates STAT3 phosphorylation through direct interaction with JAK2, thereby inhibiting its activation. Moreover, restoring the expression of STAT3 reversed the effect of AT-I on apoptosis and glycolysis in CRC cells. In vivo results revealed that AT-I significantly suppressed tumor growth in HCT116-xenografted mice. Collectively, our findings indicate that the anti-cancer activity of AT-I in CRC is associated with the induction of apoptosis and suppression of glycolysis in CRC cells, via the disruption of JAK2/STAT3 signaling. Our preliminary experimental data indicate that AT-I may have applications as a promising candidate for the treatment of CRC.